Application of comprehensive geriatric assessment in predicting early mortality among elder patients with B‐cell lymphoma receiving immunochemotherapy. (2nd July 2020) - Chou, Wen‐Chi; Chang, Hung; Wang, Po‐Nan; Kuo, Ming‐Chung; Wu, Jin‐Hou; Lin, Tung‐Liang; Su, Yi‐Jiun; Kao, Hsiao‐Wen; Ou, Che‐Wei; Hung, Chia‐Yen; Hsueh, Shun‐Wen; Hung, Yu‐Shin
Abstract: Objectives: Early mortality, defined as death within 120 days after initiated antitumor therapy, is an important issue especially for elder patients with B‐cell lymphoma. This study aimed to evaluate the clinical value of comprehensive geriatric assessment (CGA) in early mortality prediction in elderly patients with B‐cell lymphoma receiving immunochemotherapy. Methods: Seventy‐six consecutive patients with newly diagnosed B‐cell lymphoma receiving immunochemotherapy from a medical center in Taiwan were prospectively enrolled. Patients were divided into fit (n = 49) and frail (n = 27) groups per pretreatment CGA for early mortality comparison. Results: The early mortality rate in our patient cohort was 16% (n = 12): from 6% in patients with no CGA domain impairment to 43% in patients with ≥4 CGA domain impairment. The early mortality rate was 6% and 33% in fit and frail patients (odds ratio, 7.67; 95% CI, 1.86‐31.6; P = .005), respectively. Frailty was the significant predictor for early mortality in univariate and multivariate analysis. Conclusion: In this study, the number of geriatric domain impairment is positively associated with the early mortality risk in elderly patients with B‐cell lymphoma. Therefore, CGA can help clinicians to identify the risk of early mortality in elderly patients and provide alternative treatment.